Parallel electromagnetic transient simulation of power systems with a high proportion of renewable energy based on latency insertion method - Qiguo Wang; Jin Xu; Keyou Wang; Pan Wu; Weiran Chen; Zirun Li (IET Renewable Power Generation, 2023)
Abstract With the interconnection of regional grids and the increasing penetration of renewable energy, the order of the power system model is getting higher and higher, which brings great challenges to the accuracy and real‐time performance of electromagnetic transient (EMT) simulation. The simulation of power systems with a high proportion of renewable energy requires a sharp increase in the performance of the hardware platform and the parallelism of the simulation algorithm. To solve this problem, the paper proposes a fine‐grained parallel modelling method for power systems with a high proportion of renewable energy, which is inspired by the latency insertion method used in the design of large‐scale integrated circuits. And this method is implemented on GPU to achieve the component‐level and device‐level parallelized simulation of power systems with a high proportion of renewable energy. Finally, the correctness of the proposed algorithm and the CPU‐GPU cooperative architecture is verified based on an improved 118‐bus case. The cascade system of the improved 9‐bus case is used as an example to verify the superiority of the proposed algorithm in terms of simulation efficiency.